Analisis Kesalahan Penulisan Hamzah Waṣal Dan Hamzah Qaṭa‘ Pada Karangan Siswa Kelas XII MA Attarbiyah Islamiyah Kolaka - Umar, Nur Amalia; Bachtiar, Fauziah; Irfan, Irfan (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
This article examines errors in the writing of hamzah waṣal and hamzah qaṭa‘ in the compositions of twelfth-grade students as an important aspect of mastering imlā’ rules. Inaccuracy in writing hamzah indicates a limited mastery of Arabic orthographic rules, despite students having undergone both formal and nonformal Arabic language instruction. Arabic, as an international language learned by non-native speakers, often presents difficulties, particularly in writing. Therefore, this study aims to identify the forms of errors and analyze their underlying causes. This study employs a descriptive qualitative approach using error analysis as the primary analytical technique. Data were collected through writing tests, interviews, documentation, and observation, and were analyzed based on the surface strategy taxonomy and validated through triangulation. The findings reveal two types of errors, namely omission and addition, with omission as the most dominant. These findings indicate that errors in hamzah writing occur systematically. Furthermore, these errors are influenced by both linguistic and non-linguistic factors. Therefore, it is necessary to strengthen imlā’ instruction by emphasizing rule comprehension and continuous practice to improve students’ accuracy in Arabic writing